Logistična porazdelitev - Razpet, Marko (Obzornik za matematiko in fiziko, 2010)
The logistic distribution in connection with Bernoulli numbers and some other distributions are presented. The derivation of entropy formula of the logistic distribution is also given.
Keywords: Bernoullijeva števila; entropija; logistična porazdelitev; matematika; verjetnostne porazdelitve